2004
DOI: 10.1074/jbc.m306766200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pH Monitored by a New Engineered Green Fluorescent Protein Mutant

Abstract: We here describe a new molecularly engineered green fluorescent protein chimera that shows a high sensitivity to pH in the alkaline range. This probe was named mtAlpHi, for mitochondrial alkaline pH indicator, and possesses several key properties that render it optimal for studying the dynamics of mitochondrial matrix pH, e.g. it has an apparent pK a (pK a ) around 8.5, it shows reversible and large changes in fluorescence in response to changes in pH (both in vitro and in intact cells), and it is selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
154
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(176 citation statements)
references
References 32 publications
17
154
1
Order By: Relevance
“…Two observations indicate, however, that BCECF does not accumulate in the mitochondrial matrix in our preparations, but rather binds to the mitochondrial outer surface: first, incubation of ␤-escinpermeabilized preparations with membrane-impermeable BCECF stains mitochondria in a similar way as BCECF-AM loading of intact preparations and, second, a resting pH i of ~7.5 (see below) argues against the possibility that we have recorded intramitochondrial pH. In the mitochondrial matrix, pH amounts to >8.0 (Abad et al, 2004). These observations and our conclusion that the punctate fluorescence in permeabilzed salivary glands monitors pH changes in the bath reliably support a previous suggestion, derived from a slightly different experimental approach in other cell types (Weinlich et al, 1998), that BCECF reports cytoplasmic pH despite its non-homogeneous intracellular distribution.…”
Section: Methodological Aspectsmentioning
confidence: 79%
“…Two observations indicate, however, that BCECF does not accumulate in the mitochondrial matrix in our preparations, but rather binds to the mitochondrial outer surface: first, incubation of ␤-escinpermeabilized preparations with membrane-impermeable BCECF stains mitochondria in a similar way as BCECF-AM loading of intact preparations and, second, a resting pH i of ~7.5 (see below) argues against the possibility that we have recorded intramitochondrial pH. In the mitochondrial matrix, pH amounts to >8.0 (Abad et al, 2004). These observations and our conclusion that the punctate fluorescence in permeabilzed salivary glands monitors pH changes in the bath reliably support a previous suggestion, derived from a slightly different experimental approach in other cell types (Weinlich et al, 1998), that BCECF reports cytoplasmic pH despite its non-homogeneous intracellular distribution.…”
Section: Methodological Aspectsmentioning
confidence: 79%
“…According to these data, if the Ca 2ϩ influx may take part along with a hardly monitorable H ϩ efflux, the subsequent peroxisomal acidification of the lumen suggests that Ca 2ϩ re-extrusion occurs, directly or indirectly, in exchange with H ϩ . Such a prolonged compensatory response of the organelle in part recalls what happens in mitochondria where transitory alkalinization of the mitochondrial matrix occurs when Ca 2ϩ -mobilizing agents are added (29).…”
Section: Subcellular Targeting and Validation Of Peroxisomalmentioning
confidence: 99%
“…First, it was found that absorbance and°uorescence of GFP mutants strongly depend on pH value both in vitro as well as in intracellular compartments of live cells. 39,40 Probable reason could be that pH can shift equilibrium between two existing GFP ground states, which has di®erent spectroscopic characteristics. 39 For instance, the response of°uorescence of GFP mutant GFP-F64L/S65T to pH changes is rapid and reversible in the range between 6.5 and down to 5.0.…”
Section: Monitoring Intracellular Ph Level Temperature and Protein Cmentioning
confidence: 99%